Implementation Of Technology In Developing Entrepreneurship And Innovation - Agit, Alamsyah; Wahyu, A. Rio Makkulau; Octavianty, Octavianty; Abbas, Subhan Akbar; Sunarta, Desy Arum (JURNAL EKBIS, 2024)
Technology have become a very fundamental part of human daily activity including economic activity. Technology especially information technology contain numerous even infinite information which can be easily accessed. This are making learning process becoming more flexible and more independent, which allow people to learn anything from anywhere. The presence of technology are known to contribute a lot to economic activities which one of them are production process and transaction process. In process of using technology, the information in the internet have the capability to influence entrepreneurship of one person to another. So do innovation, information that can be easily accessed give the ability for someone to think critically and generate ideas, innovation even further invention. This paper purposes is to discover the process of technology in influencing both entrepreneurship and innovation. The finding of this research indicate two major finding which is technology influence entrepreneurship through it simplicity and convenience. Meanwhile innovation are influence by technology by the information it contains, providing many people to learn and finally helping in generating ideas for innovation.